Local Governance and Education Performance : A Survey of the Quality of Local Education Governance in 50 Indonesian Districts - World Bank (Washington, DC, 2014)
In the last 15 years, Indonesia has introduced a comprehensive package of education reforms designed to expand access and improve quality. A key component of the reform process has been the devolution of responsibility for basic education services to local governments and schools. The ability of local governments to deliver good quality basic education services varies considerably across Indonesia. Identifying the key dimensions of governance that underpin effective education service delivery can provide a starting point for addressing existing weaknesses and raising education performance. The main purpose of this report is to assess the state of local education governance in a sample of Indonesian districts and how it affects education performance. The study uses a unique survey of 50 local governments conducted in 2009 and 2012, coupled with district level information from household surveys, to identify patterns and explore trends in the relationship between governance and education outcomes. The report also explores the effects of a large donor supported program that aimed to strengthen the capacity of local governments. The findings of the Indonesian Local Education Governance (ILEG) survey demonstrate the importance of the quality of local governance in improving district education performance. Recent governments have demonstrated a commitment to education that has been backed up by substantial increases in public investment. The challenge for the education sector is to translate this commitment and increased investment into better education outcomes. The report has shown that strengthening the capacity of local governments to deliver good quality basic education services needs to be at the heart of efforts to address this challenge.